Turkish Adaptation of Cyberbullying Scale - Küçük, Selda; İnanıcı, Mehmet Akif and Ziyalar, Neylan (The Bulletin of Legal Medicine, 2017)
Objective: Cyberbullying is all of technically or relationally endamaging behaviors that are exhibited to an individual or a group, a specific or a legal entity by using information and communication technologies. It is observed questionnaire type of classification or sorting type of measuring tools are mostly used in terms of cyberbullying abroad. The aim of the study is to make Turkish adaptation of ‘Cyberbullying Questionnaire’ that is developed by Stewart at al. Materials and Methods: This survey is carried out in 5 public and 2 private schools depended on the Ministry of Education in Pendik district of Istanbul city. 633 students who study in 9th, 10th, 11th and 12th grades of the chosen schools construct the sample of the study. In the research, Socio-demographic Information Form and Cyberbullying Scale are used as data collection tool through face to face application. The findings obtained are analyzed via SPSS 21 statistical software.Results: The coefficients of “Factor Analysis” and “Cronbach Alpha” are calculated as validity-reliability tests. After factor analysis, coefficient of total internal consistency of the scale consisted of 13 items is calculated as crα=.87. The coefficients of the factors’ internal consistency are calculated as crα=.85 for the first factor and crα=.74 for the second one. With the total scores gathered from Cyberbullying Scale, the relationship between severity of being disturbed by other children and disturbing other children in the internet environment is found positively (r=0,48) meaningful.Conclusion: Cyberbullying Scale, which has adapted to Turkish is evaluated as applicable and has high internal consistency